THE ROLE OF DATA ANALYTICS IN ENHANCING YOUTH EMPLOYMENT IN UZBEKISTAN - Sakinabonu Aliyeva (Journal Park Publishing, 2025)
This paper investigates how data analytics can be harnessed to improve youth employment outcomes in Uzbekistan. Combining descriptive statistics, labor-market indicators for 2024–2025, and an evidence-based review of analytical methods, the article diagnoses core problems (skills mismatch, information asymmetry, regional disparities), describes practical analytics workflows (data collection, cleaning, modeling, visualization), and offers short, medium, and long-term policy recommendations. Key indicators show that youth face substantially higher unemployment and lower labor-market attachment than the general population; the paper argues that integrated data systems and analytics capacity are essential to close these gaps and to operationalize targeted interventions.
Keywords: data collection, cleaning, modeling, visualization